Premature termination codon: a tunable protein translation approach - Xiyao Cheng; Ting Zhou; Zixin Yang; Jingjing Zhou; Meng Gao; Yongqi Huang; Zhengding Su (BioTechniques)
Cellular protein–protein interactions are largely dependent on the activities of signaling proteins. Here, we present a technique to tune gene expression at translation level based on G418-inducible readthrough premature termination codon (PTC-on). To demonstrate how this PTC-on can control the expression level of a cellular signaling protein to regulate signal transduction, we settled a p53 PTC-on system in p53-null H1299 cells. After treating with G418, the cells expressed full-length p53 protein in a dose-dependent manner. We further demonstrated to use this PTC-on approach to dissect p53-dependent and p53-independent apoptosis in response to the DNA double strand breaks in H1299 cells. In principle, the PTC-on can be used as a general approach for exploring the functions of any other signaling proteins.